Recherche universitaire et priorités nationales: l’effet du financement public sur la recherche en énergie solaire au Canada - Dalpe, Robert; Gingras, Yves (Canadian Journal of Higher Education, 1990)
The role of the two main sources of university research financing in the area of solar energy ( the Strategic Grants of the NSERC and the solar energy Programs of Energy, Mines and Ressources) is examined in order to assess whether they oriented research in the direction of government programs. The applied methodology aims at establishing a relationship between inputs (financing) and outputs (scientific publications). The strongest ties seem to bind researchers having published in journals specialized in solar energy with those financed by NSERC. During the first years of the period under study, the number of publications and subsidies have both considerably increased. A scientific community on solar energy emerges and acquires the capacity to tap several different sources of financing.